Application Of Lactic Acid, Nisin And Chitosan On Quality Of Prawn (Fenneropenaeus Merguiensis) - Shirazinejad, Alireza (2013)
The effects of selected organic acids (lactic, ascorbic, citric and malic acids) on retarding bacterial spoilage of refrigerated prawns were studied. Lactic acid, applied at a level of 2% (v/v) in the ratio of 1:2 (prawn:lactic acid solution; w/v), had no adverse effects on the organoleptic properties of prawn but inhibited the growth of undesirable microorganisms. Lactic acid (2% v/v) in combination with nisin (0.04 g/L or 1600 IU/mL) exhibited pronounced inhibitory effects on Pseudomonas spp and H2S-producing bacteria which were the main spoilage microorganisms in refrigerated stored prawn. The permeabilizing effect of lactic acid (leading to liberation of lipopolysacchardes from bacterial outer membranes) on Shewanella putrefaciens (identified as a major spoilage bacterium in prawn) was enhanced by the presence of nisin.